Hierarchy of motives and structure of motivation for the use of electronic social networks by students - Tkachov, Ivan V. (Journal of the Belarusian State University. Philosophy and Psychology, 2025)
The peculiarities of the hierarchy of motives and the structure of motivation for the use of electronic social networks (ESN) by students depending on their gender, age and level of communicative competency have been determined. It was found that women, in comparison with men, give priority to the motives «social connectedness», «follower and observation of others» and «self-expression»; the structure of their motivation is more organised than the structure of men’s motivation for the use of ESS. It is indicated that in the hierarchy of motives for the use of these media platforms by students 17–19 years old, in contrast to the hierarchy of motives, typical of students 20–25 years old, the motives «self-expression» and «new friendships» are placed on different levels; instrumental motives instrumental motives («academic purposes» and «information») have a greater weight in the structure of motivation of the younger group representatives’ appeal to ESN than in this structure of motivation, belonging to the older group of respondents; the motive «self-expression» plays a greater role in the structure of motivation for the use of ESS by students 20–25 years old. It was revealed that the motives «entertainment» and «social connectedness» occupy a higher position in the hierarchy of motives for the use of ESN, characteristic of students with a low level of communicative competency, than for students with its medium and high levels. It has been noted that the structure of motivation for the use of these media platforms by students with high indicators of communicative competency is less organised, i. e. the use of ESN by these respondents is more differentiated.
Keywords: motives for the use of electronic social networks; communication competency; hierarchy of motives; motivation structure; students